Überlegungen zum Wortbildungspotenzial des Lexems frisch im deutschen - Čuden, Darko (Linguistica (Ljubljana), 2019)
The German morpheme and lexeme frisch shows, in spite of its relatively sparse distribution in the German lexicon, a surprising diversity, which can be seen both on the morphological level (frisch can be an independent unit or part of a noun, verb, adjective, adverb and even an interjection) and in terms of word formation. In the ten-volume Duden dictionary there can be found five meanings of the adjective frisch. The semantically relatively limited frisch in adjectival compounds allows, however, unlimited potential for linguistic creativity (internetfrisch probably from Internet frisch renoviert?) in response to real-world changes. The first constituent in adjectival frisch-compounds is in most cases a noun. The use of frisch-is surprisingly noticeable in the language of hunting. The lexical-semantic compatibility of frisch-adjectives with the following noun is quite limited and relatively predictable. Polysemy of frisch-adjec-tives is rather rare. The use of frisch in adjectival compounds also presents some genre-specific features. Finally, frisch appears in family names and has been used creatively in many works of literature.
Keywords: adjectival compounds; constituent; hunting; lovstvo; odzadnji slovar; pomenska vezljivost; pridevniška zloženka; retro-grade dictionary; semantic compatibility; sestavina